1995
DOI: 10.1128/aac.39.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the vanA gene cluster in clinical isolates of enterococci from the northeastern United States

Abstract: In several strains of Enterococcus faecium isolated in Europe, the cluster of genes encoding high-level resistance to vancomycin (VanA phenotype) resides on a 10.85-kb transposon, Tn1546, or closely related elements. To determine whether Tn1546 was conserved in recent enterococcal isolates from the northeastern United States, seven strains were compared by restriction mapping and DNA hybridization with probes from within the van cluster. Two of the seven strains contained intact Tn1546-like sequences; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
121
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 29 publications
(29 reference statements)
8
121
1
2
Order By: Relevance
“…The heterogeneity of the Tn1546-like element results from point mutations, deletions, and the integration of insertion sequence (IS) elements (16,17); and among these variations, the presence of IS elements accounts for much of the heterogeneity (3). Such a rearrangement has been shown to play a key role in the evolution of the vanA gene cluster and may modify its transferability (7,8,11). In the present study, we characterized the consequence of Tn1546 in vanA-containing Enterococcus faecium isolates collected from patients over time passed to obtain an understanding of the hospital dissemination of VRE over time.…”
mentioning
confidence: 99%
“…The heterogeneity of the Tn1546-like element results from point mutations, deletions, and the integration of insertion sequence (IS) elements (16,17); and among these variations, the presence of IS elements accounts for much of the heterogeneity (3). Such a rearrangement has been shown to play a key role in the evolution of the vanA gene cluster and may modify its transferability (7,8,11). In the present study, we characterized the consequence of Tn1546 in vanA-containing Enterococcus faecium isolates collected from patients over time passed to obtain an understanding of the hospital dissemination of VRE over time.…”
mentioning
confidence: 99%
“…The concurrent appearance of vanA in both Europe and the United States, despite the lack of avoparcin use in the United States, suggests that the epidemiology and global dissemination of vanA are complex (38,40). Tn1546 is often associated with plasmids, and several reports have emphasized the fact that there are polymorphisms between Tn1546 elements due to insertions, deletions, and point mutations (10,13,14,(36)(37)(38)(39)42).…”
mentioning
confidence: 99%
“…This is consistent with the findings of Zhou et al (1995) who reported that IS1167 was similar to a short non-coding region in our previously published nucleotide sequence of the M5 sspB gene (Demuth et al, 1990a (Bennett, 1991). The putative transposase polypeptide is highly similar (85-95% sequence identity) to regions of both ORFl and ORF2 of IS1167 and exhibits 30-4o0/0 sequence identity with transposases encoded by IS1 165 (Johansen & Kibenich, 1992), IS1181 (Derbise et al, 1994), IS1251 (Handwerger et al, 1995) (Chandler & E:ayet, 1993). Whether the lack of these sequences in the ISSgl transposase influences its activity remains to be determined.…”
Section: Discussionmentioning
confidence: 99%